THE ELIMINATION OF STATE ADMINISTRATIVE COURT’S AUTHORITY TO DECIDE POSITIVE FICTITIOUS DECISIONS AFTER THE AMENDMENT TO LAW NUMBER 30 OF 2014 CONNECTED WITH THE GENERAL PRINCIPLES OF GOOD GOVERNANCE - Pertiwi, Adinda Putri; Rompis, Adrian E.; Nurzaman, R. Adi (Jurnal Poros Hukum Padjadjaran, 2023)
Government agencies and/or officials carry out the task of administering the state using legal instruments, one of which is decisions. If within the allotted time a government official does not respond to the request filed against him, his silence is equated with a fictitious decision. The fictitious decisions that apply in Indonesia are positive fictitious decisions, implicitly contained in Article 53 paragraph (3) of Law Number 30 of 2014, namely the government's silence means a form of acceptance. A positive fictitious decision needs to be submitted to the Administrative Court to get an acceptance decision. After the UUCK, PTUN's authority to decide on positive fictitious decisions was abolished, so what are the legal consequences and whether this is in accordance with the AUPB. The research method uses normative juridical with statutory, case, and conceptual approaches. The results of the research show that PTUN does not have the authority to decide on a positive fictitious decision request due to the abolition of Article 53 paragraph (4) in UUCK, so that the settlement lies with government agencies. However, there is a disparity in the judge's decision regarding the authority of PTUN to decide on a positive fictitious decision request caused by two approaches, namely legalistic positivism and action. It is possible to enter a positive fictitious case by filing a lawsuit for unlawful acts by government agencies and/or officials. The abolition of PTUN's authority is not in accordance with AUPB, especially the principles of legal certainty, expediency, accuracy, and fairness.